Vorratsbomben im Himmel. Über digitalen Terror, unsichtbare Opfer und die Rhetorik der Präzision - Weber, Jutta (Kriegsmaschinen. Roboter im Militäreinsatz)

Techno-Security, Risk and the Militarization of Everyday Life - Weber, Jutta (The Computational Turn: Past, Presents, Futures? Proceedings of the International Association for Computing and Philosophy. Aarhus University July 4-6, 2011)

Gefährten, Gedankenleser, Geeks. Mensch-Maschine-Beziehungen in der Technoscience - Weber, Jutta (Körper Raum Transformation. Gender-Dimensionen von Natur und Materie)

Technologien der (Un-)Sicherheit - Weber, Jutta; Allhutter, Doris (Newsletter des Österreichischen Instituts für Technikfolgenabschätzung, ITA-News September 2011)

Interdisziplinierung? Zur Übersetzungspolitik einer neuen Technowissenschaftskultur - Weber, Jutta (Interdisziplinierung? Über den Wissenstransfer zwischen den Geistes-, Sozial- und Technowissenschaften)

Interdisziplinarität und Interdisziplinierung. Eine Einleitung - Weber, Jutta (Interdisziplinierung? Über den Wissenstransfer zwischen den Geistes-, Sozial- und Technowissenschaften)

Virtual Prototyping software-intensiver mechatronischer Systeme - Eine Fallstudie - Becker, Markus; Zabel, Henning; Müller, Wolfgang; Elfeky, Ahmed

A SystemC Based Library for Functional Coverage - Kuznik, Christoph; Müller, Wolfgang

A Reconfiguration Approach for Faul-Tolerant FlexRay Networks - Klobedanz, Kay; König, Andreas; Müller, Wolfgang (Proceedings of DATE'11)
In this paper we present an approach for the configuration and reconfiguration of FlexRay networks to increase their fault tolerance. To guarantee a correct and deterministic system behavior, the FlexRay specification does not allow a reconfiguration of the schedapproachule during run time. To avoid the necessity of a complete bus restart in case of a node failure, we propose a reconfiguration using redundant slots in the schedule and/or combine messages in existing frames and slots, to compensate node failures and increase robustness. Our approach supports the developer to increase the fault tolerance of the system during the design phase. It is a heuristic, which, additionally to a determined initial configuration, calculates possible reconfigurations for the remaining nodes of the FlexRay network in case of a node failure, to keep the system working properly. An evaluation by means of realistic safety-critical automotive real-time systems revealed that it determines valid reconfigurations for up to 80% of possible individual node failures. In summary, our approach offers major support for the developer of FlexRay networks since the results provide helpful feedback about reconfiguration capabilities. In an iterative design process these information can be used to determine and optimize valid reconfigurations.
Keywords: Schedules; Fault tolerant systems; Redundancy; Protocols; Automotive engineering; Genetic algorithms

Empirische Forschung und Soziale Arbeit. Ein Studienbuch.
Empirische Forschung in der Sozialen Arbeit gewinnt immer weiter an Intensität und Breite, ebenso an zunehmender Qualität. Dies verdeutlichen die Beiträge in diesem Band. Das Studienbuch eröffnet Einblicke in konkrete Forschungsprojekte und damit zugleich in die aktuelle Landschaft empirischer Forschung in der Sozialen Arbeit. Vorgestellt werden sowohl quantitative als auch qualitative Studien zu verschiedenen Thematiken und Handlungsfeldern Sozialer Arbeit, ebenso unterschiedliche methodische und methodologische Vorgehensweisen. Der Band umfasst exemplarische Untersuchungen mit ihren Forschungsfragestellungen, methodischen Konzeptionen und Ergebnissen. Darüber hinaus werden in Forschungsessays übergreifende Perspektiven empirischer Forschung diskutiert und schließlich in methodischen Beiträgen ausgewählte Datenerhebungs- und Auswertungsverfahren mit Bezug auf konkrete Forschungsprojekte anschaulich dargestellt.
Keywords: Ethnographie Kinder- und Jugendhilfe Methoden Sozialpädagogik Sozialraum

Ökonomische Möglichkeiten und Auswirkungen von Wettbewerb bei Zentralverwahrern für Bundeswertpapiere. Gutachten im Auftrag des Bundesministeriums für Finanzen (BMF). Gutachten fg 1/10 - Uhde, André; Haucap, Justus; Heimeshoff, Ulrich

The nexus between monetary policy, banking market structures and bank risk-taking - Uhde, André; Michalak, Tobias
Using a sample of stock-listed bank holding companies located in Western Europe over the period from 1997 to 2008 this paper provides empirical evidence that an increase in short-term interest rates as well as an extended period of expansionary monetary policy has a negative impact on European stock-listed banks’ soundness as measured by the Expected Default Frequency. Against this background and in order to evaluate interactions between the risk-taking channel of monetary policy and the competitiveness of a country’s banking market we find a negative impact of an increase in competition in the loan market – proxied by the Boone-indicator – on financial soundness. Referring to the structural-conduct performance (SCP) paradigm, this paper provides further evidence that an increase in concentration in the banking market spurs financial soundness.

Doing Gender: Sprachliche Formen – kommunikative Funktionen – kulturelle Traditionen - Schuster, Britt-Marie (Geschlechterforschung. Theorien, Thesen, Themen zur Einführung)

Zugezogene im Fokus. Eine empirische Studie - Lorenz, Cornelia (Perspektiven der Variationslinguistik. Beiträge aus dem Forum Sprachvariation)

Liquid-Phase Epitaxy of Multicomponent Layer-Based Porous Coordination Polymer Thin Films of [M(L)(P)0.5] Type: Importance of Deposition Sequence on the Oriented Growth - Zacher, Denise; Yusenko, Kirill; Bétard, Angèlique; Henke, Sebastian; Molon, Mariusz; Ladnorg, Tatjana; Shekhah, Osama; Schüpbach, Björn; de los Arcos de Pedro, Maria Teresa; Krasnopolski, Michael; Meilikhov, Mikhail; Winter, Jörg; et al. (Chemistry - A European Journal)

Influence of process parameters on the crystallinity, morphology and composition of tungsten oxide-based thin films grown by metalorganic chemical vapor deposition - de los Arcos de Pedro, Maria Teresa; Cwik, Stefan; Milanov, Andrian P.; Gwildies, Vanessa; Parala, Harish; Wagner, Tristan; Birkner, Alexander; Rogalla, Detlef; Becker, Hans-Werner; Winter, Jörg; Ludwig, Alfred; Fischer, Roland A.; et al. (Thin Solid Films)

Evaluation of Homoleptic Guanidinate and Amidinate Complexes of Gadolinium and Dysprosium for MOCVD of Rare-Earth Nitride Thin Films - Thiede, Tobias B.; Krasnopolski, Michael; Milanov, Andrian P.; de los Arcos de Pedro, Maria Teresa; Ney, Andreas; Becker, Hans-Werner; Rogalla, Detlef; Winter, Jörg; Devi, Anjana; Fischer, Roland A. (Chemistry of Materials)

X-ray photoelectron spectroscopy on implanted argon as a tool to follow local structural changes in thin films - Lahrood, Atena Rastgoo; de los Arcos de Pedro, Maria Teresa; Prenzel, Marina; von Keudell, Achim; Winter, Jörg (Thin Solid Films)

Dada-Zürich. Ästhetische Theorie der historischen Avantgarde. - Bergmeier, Horst

Der souveräne Mensch. Die Anthropologie Heinrich von Kleists. - Müller, Tim